Ruptured aneurysm in the posterior communicating segment of carotid artery presenting with contralateral oculomotor nerve palsy - Finger, Guilherme (2019)
Background: Brain aneurysms are mostly discovered during the investigation of subarachnoid hemorrhage (SAH). Some patients present neurological signs that may suggest the aneurysm’s topography, and the oculomotor nerve palsy (ONP) of the same side of the aneurysm is the most common sign. Only one case report of contralateral palsy was previously described in the medical literature. Case Description: Authors describe a patient who presented a classic manifestation of SAH associated with complete ONP, whose vascular investigation demonstrated a brain aneurysm located in the contralateral intracranial carotid. The patient was surgically treated with great neurologic outcome, and late angiography did not evidence other vascular abnormalities. Conclusion: The ipsilateral ONP is a common sign found in posterior communicating artery aneurysms; however, such aneurysm can have different presentations due to the elevation of intracranial pressure, and, in rarer cases, the ONP cannot be operated as a localizing sign.